A Trinitarian modal-spherical method of apologetics and cultural redemption: perspectives on religion and contemporary culture - Braun, Guilherme Junior (University of the Free State, 2016)
The following study of focus areas is an application of the recently developed Trinitarian modal-spherical method of apologetics, TMSA (Braun 2013), to the field of Religious Studies. The trajectory to be pursued will make use of basic sources in the presentation of three focus areas of contemporary culture: (a) Technology and everyday experience, (b) music and popular culture and (c) romantic love and economic freedom. Further, the philosophical deepening into the presented focus areas will be sought through the dialogue between continental and reformational philosophy as well as the integration of insights. Gained insights and conclusions from this dialogue will then be presented in terms of TMSA‟s Christian (confessional) stance. Main goals of this study are (I) to demonstrate how the ego's religious orientation manifests itself in the focus areas concerned (II) as well as to point out redemptive ways of dealing with them, as central sites of the contemporary lifeworld, through TMSA‟s Neo-Calvinist vision. As such, this study was designed in order to provide points of entry for the approach of contemporary human beings and their culture via TMSA. Accordingly, it isn't thereby intended to deliver the "full picture" of the subjects concerned, but rather, new possibilities of dialogue will be opened up (from TMSA‟s radically Christian perspective). Therefore, as the main priority of this study is the application of TMSA, basic sources will come into play as to enable an approximation of the contemporary lifeworld and the chosen focus areas.

Die volgende studie van fokusareas is 'n toepassing van die onlangs ontwikkelde Trinitariese modaal-sferiese metode van apologetiek, TMSA (Braun 2013), op die gebied van Religiestudies. Die trajek wat nagestreef word, sal gebruik maak van basiese bronne in die aanbieding van drie fokusareas van kontemporêre kultuur: (a) Tegnologie en alledaagse ervaring, (b) musiek en populêre kultuur en (c) romantiese liefde en ekonomiese vryheid. Verder sal die filosofiese verdieping in die voorgestelde fokusareas gesoek word deur die dialoog tussen kontinentale en reformatoriese filosofie, sowel as die integrasie van insigte. Die insigte en gevolgtrekkings wat uit hierdie dialoog verkry word, sal dan aangebied word in terme van TMSA se Christelike (konfessionele) posisie. Die hoofdoelwitte van hierdie studie is (I) om te demonstreer hoe die ego se godsdienstige oriëntasie homself manifesteer in die betrokke fokusareas, (II) asook om verlossende maniere uit te wys om daarmee, as sentrale areas van die hedendaagse leefwêreld, om te gaan deur TMSA se Neo -Calvinistiese visie. As sodanig, is hierdie studie ontwerp om toegangspunte tot die benadering van die hedendaagse mense en hul kultuur via TMSA te verskaf. Gevolglik is die doel daarvan nie om die "volle prentjie" van die betrokke temas te verskaf nie, maar eerder om nuwe moontlikhede vir dialoog te open (vanuit TMSA se radikaal Christelike perspektief). Daarom, aangesien die hoofprioriteit van hierdie studie die toepassing van TMSA is, sal basiese bronne gebruik word om dit moontlik te maak om nader aan die hedendaagse leefwêreld en die gekose fokusareas te kom.
Thesis (Ph.D. (Religion Studies))--University of the Free State, 2016
Keywords: Heidegger; De Vries; Taylor; Ihde; Dooyeweerd; Strauss; Cultural redemption; Contemporary lifeworld; Contemporary culture; Philosophy of technology; Everyday experience; Human-technology relationships; Revelation; De Nora; Schopenhauer; Nietzsche; Adorno; Music philosophy; Popular culture; Illouz; Rand; Stoker; Ive; Baader; Romantic love; Erotic philosophy; Capitalism; Economic freedom; Neo-Calvinism; Reformational philosophy; Continental philosophy; TMSA; Trinity